Health and wellbeing Benefits of Urban Agriculture Practice in Kathmandu Valley - Shrestha, Marina Vaidya; Shrestha, Sunil Babu; Shrestha, Bijaya (Journal of Nepal Health Research Council, 2025)
Background: Urban areas are occupied with dense population and green spaces are hard to find. Urban agriculture solves food security problems as well as has important positive health outcomes. The aim of this study is to determine health and wellbeing Benefits of Urban Agricultural Practice.Methods: A cross-sectional study was conducted from December 2022 to June 2023. Random selection of three study sites from Kathmandu valley was done. The total sample size was 230 which was grouped into involved in agriculture (115) and non- Involved in agriculture (115). Those groups were recruited from different wards of Kathmandu, Lalitpur and Bhaktapur. Questionnaire regarding socio-demographic variables, SF-12 health survey, perceived stress scale, satisfaction with life scale were used. KoBo Toolbox was used for data collection.Results: The involved in agriculture groups differed from non-involved in terms of gender, ethnicity, occupation, marital status, education and ownership of the house (p<0.05). Participants engaged in urban agriculture reported significantly lower levels of perceived stress compared to those not involved in urban agriculture. Similarly, the data shows that life satisfaction was significantly higher among the group involved in urban agriculture. Conclusions: Urban agriculture was associated with lower perceived stress and higher life satisfaction among the study participants who were involved in urban agriculture compared to the group not involved as compared to the group of study participants not involved in urban agriculture.Keywords: Agriculture; cities; healthcare; urban population.